Pannelli a “Sensorialità Aumentata” sull’Appia Antica: cronistoria, principi, realizzazione di un metodo innovativo - Rosati, Paolo (Archeomatica, 2023)
On 24 September 2022, two sensory panels were inaugurated along the Appia Antica at the third mile, in front of the church of S. Nicola. They are visible with your back to the entrance to the Mausoleum of Cecilia Metella.